Cadherins and catenins in cancer: connecting cancer pathways and tumor microenvironment - Lin, Wan-Hsin; Cooper, Lisa M.; Anastasiadis, Panos Z. (Frontiers in Cell and Developmental Biology, 2023)
Cadherin-catenin complexes are integral components of the adherens junctions crucial for cell-cell adhesion and tissue homeostasis. Dysregulation of these complexes is linked to cancer development via alteration of cell-autonomous oncogenic signaling pathways and extrinsic tumor microenvironment. Advances in multiomics have uncovered key signaling events in multiple cancer types, creating a need for a better understanding of the crosstalk between cadherin-catenin complexes and oncogenic pathways. In this review, we focus on the biological functions of classical cadherins and associated catenins, describe how their dysregulation influences major cancer pathways, and discuss feedback regulation mechanisms between cadherin complexes and cellular signaling. We discuss evidence of cross regulation in the following contexts: Hippo-Yap/Taz and receptor tyrosine kinase signaling, key pathways involved in cell proliferation and growth; Wnt, Notch, and hedgehog signaling, key developmental pathways involved in human cancer; as well as TGF- and the epithelial-to-mesenchymal transition program, an important process for cancer cell plasticity. Moreover, we briefly explore the role of cadherins and catenins in mechanotransduction and the immune tumor microenvironment.